The Non-adaptive Pathologies and Their Neuroendocrine, Mnemic and Clinical Expression - Paiva Neto, Arnaldo P. G. de (International Journal of Innovative Research in Medical Science, 2019)
The article revises the origin of neurosteroids as production of nervous tissue or "neuroactive steroids" that migrate into the nervous system. Our objective is to explain the adequacy between the neuro-sensory system and the metabolic-motor system. We adopted an explicative research with practical and experimental reports, from hospital observations. This type of analysis attempts to explore the hypothalamic-pituitary-adrenal axis (or HPA axis). There is evidence that bone marrow cells migrate to white matter, hippocampal neurons and cerebral cortex participating in tissue regeneration, primarily linked to memory formation. This formation indicates that the rhythm of the activated brain area is synchronized with the stimuli that excited it. Our whole neuroendocrine system works in sequenced cycles. Any disorder compromises the mnemic function. There is an inhibitory influence of corticosterone on the expression of PSA-NCAM (which is responsible for the neurogenesis in the hippocampal region). Pregnenolone sulfate reverses aging-related memory deficits in rat studies. The steroid dehydroepiandrosterone (DHEA) inhibits the action of glucocorticoids and makes it possible to ameliorate the immunosuppressive effects of chronic stress. Serum levels of DHEA divided by serum levels of cortisol can be used to correlate with the degree of quality in aging.